Penerapan Pembelajaran Berdiferensiasi Dalam Kurikulum Merdeka Pada Mata Pelajaran al-Qur’an Hadis di Kelas VII MTsN Pasaman - Y, Yelpina; M, Iswantir (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The rationale behind this study stems from the fact that MTsN 5 Pasaman is still having issues with differentiated learning implementation. Specifically, teachers are still struggling to map students' learning styles accurately, implement the program in a way that meets students' needs, and maximizes learning outcomes. The aim of this study is to investigate the application, implementation, and differentiated learning results in Al-Qur'an Hadith courses at MTsN 5 Pasaman's autonomous curriculum. Data gathering, data reduction, data presentation, and data verification are the methods of data analysis that are used. The research's findings demonstrate how differentiated learning is implemented in the independent curriculum for Al-Qur'an Hadith subjects at MTsN 5 Pasaman. Specifically, learning styles are mapped out in the learning planning process, and learning needs are accommodated based on students' learning styles. The effectiveness of differentiated learning is evaluated through diagnostic tests.